MGL Receptor and Immunity: When the Ligand Can Make the Difference - Ilaria Grazia Zizzari; Chiara Napoletano; Federico Battisti; Hassan Rahimi; Salvatore Caponnetto; Luca Pierelli; Marianna Nuti; Aurelia Rughetti (Journal of Immunology Research)
C-type lectin receptors (CLRs) on antigen-presenting cells (APCs) facilitate uptake of carbohydrate antigens for antigen presentation, modulating the immune response in infection, homeostasis, autoimmunity, allergy, and cancer. In this review, we focus on the role of the macrophage galactose type C-type lectin (MGL) in the immune response against self-antigens, pathogens, and tumor associated antigens (TAA). MGL is a CLR exclusively expressed by dendritic cells (DCs) and activated macrophages (MØs), able to recognize terminal GalNAc residues, including the sialylated and nonsialylated Tn antigens. We discuss the effects on DC function induced throughout the engagement of MGL, highlighting the importance of the antigen structure in the modulation of immune response. Indeed modifying Tn-density, the length, and steric structure of the Tn-antigens can result in generating immunogens that can efficiently bind to MGL, strongly activate DCs, mimic the effects of a danger signal, and achieve an efficient presentation in HLA classes I and II compartments.